Autonomy, Good Humor and Support Networks, Potential of Community Resilience Intervention in People Victims of the Earthquake in the CalderÃ³n Parish - Meza, Anicia Katherine Tarazona; Freyre, JoaquÃƒÂn RamÃƒÂ³n Alonso; Cevallos, Miguel Giancarlo Ormaza; Pico, MarÃƒÂa Joaquina Mera (International Research Journal of Management, IT & Social Sciences, 2018)
Resilience is a concept widely used in recent years, especially when it comes to evaluating the level of recovery of communities that are hit by natural phenomena. It can be stated that conceptually resilience constitutes the ability to react effectively and quickly to the effects of disasters, being a complex phenomenon to evaluate and define. And although the level of resilience does not necessarily imply greater control of vulnerability, it can be affirmed that the reduction of vulnerable conditions can strengthen and consolidate the resilient capacity of individuals and communities, in the face of the effects of natural disasters.